Reception Analysis of Dr. Boyke’s Reproductive Health Messages on TikTok Among Communication Science Students at Universitas Trunodjoyo Madura - Rafi Joan Pratama; Febiana Putri; M. Jamaluddin Ali Wafi (Yayasan Citra Dharma Cindekia, 2026)
The evolution of social media has brought major changes in how the public obtains information, including reproductive health data. TikTok has emerged as a widely used platform for educational content due to its brief, engaging, and digestible videos that resonate with the younger generation. Dr. Boyke Dian Nugraha is a prominent figure actively providing reproductive health education on this platform. This study aims to discover how Communication Science students at Universitas Trunodjoyo Madura interpret Dr. Boyke's reproductive health messages on TikTok and to identify the factors influencing this meaning-making process. Utilizing a qualitative approach rooted in Stuart Hall’s reception analysis, informants were selected via purposive sampling. The criteria included active UTM Communication Science students who use TikTok and have accessed Dr. Boyke’s reproductive health content. Data were gathered through in-depth interviews, non-participatory observation, and documentation. The results indicate that students decode reproductive health messages into three distinct reading positions: dominant-hegemonic, negotiated, and oppositional. Variations in interpretation are driven by personal experience, existing knowledge of reproductive health, social environments, and the intensity of social media usage. These findings highlight TikTok's significant potential as an educational tool for youth reproductive health. However, message effectiveness is determined not just by content, but by the audience's background and characteristics during interpretation.